1991
DOI: 10.1002/aja.1001920411
|View full text |Cite
|
Sign up to set email alerts
|

The role of growth factors in the embryogenesis and differentiation of the eye

Abstract: The vertebrate eye is composed of a variety of tissues that, embryonically, have their derivation from surface ectoderm, neural ectoderm, neural crest, and mesodermal mesenchyme. During development, these different types of cells are subjected to complex processes of induction and suppressive interactions that bring about their final differentiation and arrangement in the fully formed eye. With the changing concept of ocular development, we present a new perspective on the control of morphogenesis at the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 219 publications
(214 reference statements)
1
46
0
1
Order By: Relevance
“…is the generally accepted method. 3T3 cells are either lethally irradiated or growth arrested with mitomycin C and then seeded on tissue culture dishes at 2 3 10 4 cells/cm 2 (117,118).…”
Section: Culturing Of Lescmentioning
confidence: 99%
See 1 more Smart Citation
“…is the generally accepted method. 3T3 cells are either lethally irradiated or growth arrested with mitomycin C and then seeded on tissue culture dishes at 2 3 10 4 cells/cm 2 (117,118).…”
Section: Culturing Of Lescmentioning
confidence: 99%
“…In the human embryo, the corneal epithelium is formed by the 6th gestational week, from the surface ectoderm overlying the detaching lens (2). At this stage, it consists of a twolayered epithelium that is separated from the endothelium by an acellular space, the so called primary stroma (3).…”
mentioning
confidence: 99%
“…TGF-␤, a known physiological effecter of various extracellular matrix genes and their products, is present in the aqueous and vitreous humors (90) and has been shown to induce cataracts (28,29,52). Of its three isoforms, TGF-␤1 has been shown to promote tissue fibrosis, formation of stress fiber, epithelial-mesenchymal transition (EMT), myofibroblast formation, fibrosis, and apoptosis by overstimulating genes such as extracellular matrix proteins, ␣-SMA, and ␤ig-h3, which are implicated in several pathogenic conditions (11,79,86,92).…”
mentioning
confidence: 99%
“…The in¯uence exerted by these edges on differentiation of the lens ®bres has been reported (Tripathi et al, 1991;Wride, 1996), and it is possible that the disappearance or diminishing of CSPG in this region favours contact between both structures and facilitates some in¯uence of the optic cup edges on the lens primordium at this stage of development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is strong evidence that FGF-2 plays a key role in lens development (McAvoy et al, 1991;Tripathi et al, 1991). It was demonstrated that, in embryonic development, there is a direct functional relationship between FGF-2 and chondroitin sulphate proteoglycan (Ruoslahti and Yamaguchi, 1991;Milev et al, 1998;Colin et al, 1999) or heparan sulphate proteoglycan (Massague, 1991;Yayon et al, 1991;Nugent and Edelman, 1992); these data suggest that the in¯uence of proteoglycans in lens development could be mediated by growth factors.…”
Section: Introductionmentioning
confidence: 98%